Injury prevention in swimming - Boyd, K. (coachesinfo.com, 2008)
Swimming is a highly popluar sport in many countries. Up to 12% of the population of the United Kingdom regularly take part. Epidemiological data suggest that overall injury rates are very low in comparison with other sports. Swimming is often promoted as an ideal activity for the acknowledged benefits of exercise for both those in health and with disease. The spectrum of swimmers, therefore, cover those individuals wishing to improve their health to the committed elite swimmer. It is this latter group that suffer from the preponderance of injuries. The swimmer needs to contend with the fact that they perform in an alien, fluid environment that offers considerable resistance to forward motion and relies largely on the uppper limbs for propulsion. The four strokes differ subtlely in their injury patterns.